Penerapan Prosedur Audit Aset Tetap dan Dampaknya terhadap Laporan Keuangan (Studi pada KAP ABC di Kota Bogor) - Lisnah Ismi Wikandari; Meysha Aulia; Fazra Danish Ara; Raden Syahira Maulidia (CV. ITTC INDONESIA, 2025)
This study examines the fixed asset audit procedures conducted by KAP ABC at Hotel XYZ and its impact on the fair presentation of the 2024 financial statements. Using a descriptive qualitative method with interviews and literature studies, the research focuses on document testing, physical observation, and depreciation verification based on PSAK 216. The audit revealed material understatements in the depreciation base by IDR 36.508.871.380 and accumulated depreciation by IDR 12.539.516.422. These discrepancies resulted from capitalization failures and inaccurate mutation recordings, causing the net book value and net profit to be overstated. The auditor's proposed adjustments successfully restored the financial statements' fairness. The study concludes that effective substantive audit procedures and strengthened internal controls are essential to mitigate the risk of material misstatements in fixed asset management.